Beyond Separate Emergence: A Systems View of Team Learning Climate - Harvey, Jean-François; Leblanc, Pierre-Marc; Cronin, Matthew A. (Frontiers in Psychology, 2019)
In this paper, we consider how the four key team emergent states for team learning identified by Bell, Kozlowski and Blawath (2012), namely psychological safety, goal orientation, cohesion, and efficacy, operate as a system that produces the team’s learning climate (TLC). Using the language of systems dynamics, we conceptualize TLC as a stock that rises and falls as a joint function of the psychological safety, goal orientation, cohesion, and efficacy that exists in the team. The systems approach highlights aspects of TLC management that are traditionally overlooked, such as the simultaneous influence of and feedback between the four team emergent states and the inertia that TLC can have as a result. The management of TLC becomes an issue of controlling the system rather than each state as an independent force, especially because changing one part of the system will also affect other parts in sometimes unintended and undesirable ways. Thus the value is to offer a systems view on the leadership function of team monitoring with regards to team emergent states, which we term team state monitoring. This view offers promising avenues for future research as well as practical wisdom. It can help leaders remember that TLC represents an equilibrium that needs balance, in addition to pointing to the various ways in which they can influence such equilibrium.